2022
DOI: 10.5829/ije.2022.35.05b.01
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Analysis of Micropolar Ethylene-glycol Nanofluid on Stretching Surface Mounted Triangular, Rectangular and Chamfer Fins by FEM Strategy and Optimization with RSM Method

Abstract: This paper analysis heat transfer and angular velocity of micropolar ethylene-glycol nanofluid over the triangular, rectangular and chamfer fins on the stretching sheet. The innovation of this paper is to investigate parameters of nanofluid flow passing from the different fins on the stretching surface. The finite Element Method is selected for solving governing equations. The nanofluid temperature in the space of fins is warm and equal to the surface temperature. The temperature value is 30 degrees. The maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…They showed that adding different types and different volume fractions of nanoparticles has different effects on heat transfer properties. Pasha and Domiri-Ganji (18) analyzed heat transfer and angular velocity of micropolar ethylene-glycol nanofluid over various fins on a stretching sheet, revealing maximum temperature at the last fin and higher angular velocity for triangular and chamfer fins. Ho and Chen (19) investigated experimentally forced convection heat transfer utilizing an Al2O3-water nanofluid in a copper minichannel heat sink.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that adding different types and different volume fractions of nanoparticles has different effects on heat transfer properties. Pasha and Domiri-Ganji (18) analyzed heat transfer and angular velocity of micropolar ethylene-glycol nanofluid over various fins on a stretching sheet, revealing maximum temperature at the last fin and higher angular velocity for triangular and chamfer fins. Ho and Chen (19) investigated experimentally forced convection heat transfer utilizing an Al2O3-water nanofluid in a copper minichannel heat sink.…”
Section: Introductionmentioning
confidence: 99%
“…Abdollahzadeh et al [14] reviewed the studying the half-breed of radiation and attractive parameters on Maxwell fluid with TiO2 nanotube impact of distinctive edges. Pasha and Domiri-Ganji [15] examining the crossover examination of micropolar ethylene-glycol nanofluid on extending surface mounted triangular, rectangular, and chamfer blades by FEM technique and optimization with RSM strategy. Darezereshki et al [16] studied the chemical handle of synthesizing zinc oxide (ZnO) with nanorod and circular morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Habibzadeh et al (24) present a renewable energy system integrating solar and geothermal sources with nanofluid-based collectors, employing SiO2 and TiO2 nanoparticles, and evaluate their performance based on energy, exergy, and cost analysis, noting the impact of key parameters like solar irradiation and collector inlet temperature on efficiencies and hydrogen and freshwater production rates. There have been numerous valuable studies conducted in the fields of fluid mechanics, nanofluids, and microchannels, which are reported in the literature (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). These studies can serve as valuable resources for future research and advancements in these areas.…”
mentioning
confidence: 99%